Conjuring up prehistory : landscape and the archaic in Japanese nationalism - Hudson, Mark, 1963- (Access archaeology., 2021)
This study considers the ways in which archaeology and landscapes of the archaic have been appropriated in Japanese nationalism since the early twentieth century, focusing on the writings of cultural historian Tetsuro Watsuji, philosopher Takeshi Umehara and environmental archaeologist Yoshinori Yasuda.